EFFECT OF TREBON (ETOFENPROX) AND ITS RESIDUES IN ADULT MOSQUITO FISH, Gambusia affinis - Almashhadani, Hussain; Kaddou, Ibrahhim (Iraqi Journal of Science, 2024)
Effects of Trebon (Etofenprox) and its residues in Gambusia affinis were investigated .The fish were exposed to various doses of the insecticide during aperiod of 96 hours. The LC50 was 0.027 mg / l . Residues of Trebon in tissues of fishes weighting 0.35 g exposed to high concentration of the insecticide in water which killed 100% of the fish was 0.02696 mg/g fish as analysed by the UV-visible spectrophotometer.